Evaluation of vitamin D levels and body mass indexes of university employees (Bangladesh Journal of Medical Science, 2020)
Objective: Vitamin D is known to have important effects on human health. The existence of a relationship between obesity and vitamin D levels, which have been shown to cause a number of health problems with various studies, is certain. In this study, the relationship between vitamin D levels and body mass indexes(BMI) of individuals was evaluated. The study is unique for being the only research on literature that carried out with university employees.Materials and methods: Blood samples, anthropometric measurement (BMI) was obtained from 87 volunteer working at Haliç University. The questionnaire form covering the basic questions applied by means of face-to-face method. Quantification of the analytes for 25-hydroxyvitamin-D was carried out using LC-MS/MS. The relationship between 25-hydroxyvitamin-D values and BMI was evaluated with Tukey HSD multiple comparison test. 95% confidence and 80% power sampling were applied to the predictions of a minimum0.50 connection coefficient between 2 quantitative variables.The necessity of 30 cases was determined by using the N = [(Zα+Zβ)/C]2 + 3formula.Considering the losses, the work will be carried out over 80 people.Results and Discussion: There’s significant difference between 25-hydroxyvitamin-D2 and 25-hydroxyvitamin-D3 and the BMI levels of the subjects(p:0.028